2007
DOI: 10.1063/1.2751923
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Scanning Probe Microscopy to Investigate Crystal-Fluid Interfaces

Abstract: Abstract. Over the past decade there has been a natural drive to extend the investigation of dynamic surfaces in fluid environments to higher resolution characterization tools. Various aspects of solution crystal growth have been directly visualized for the first time. These include island nucleation and growth using transmission electron microscopy and scanning tunneling microscopy; elemental step motion using scanning probe microscopy; and the time evolution of interfacial atomic structure using various diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…These results are in agreement with a previous AFM study in which the growth rate of brushite was shown to be inversely proportional to Ca/PO 4 ratio in the solution [25]. Further, Kokubo's [26] classical method of producing HAP precipitate on the surface of a bioglass immersed in simulated body fluid (SBF; [Ca 2 + ]¼2.5 mM, [H x PO 4…”
Section: Resultssupporting
confidence: 90%
“…These results are in agreement with a previous AFM study in which the growth rate of brushite was shown to be inversely proportional to Ca/PO 4 ratio in the solution [25]. Further, Kokubo's [26] classical method of producing HAP precipitate on the surface of a bioglass immersed in simulated body fluid (SBF; [Ca 2 + ]¼2.5 mM, [H x PO 4…”
Section: Resultssupporting
confidence: 90%
“…First of all, HAp is typified by incongruent dissolution, releasing more Ca 2+ than PO 4 3− in the acidic milieu and more PO 4 3− than Ca 2+ under alkaline conditions 62 . Conversely, formation of phosphate network is the first step in nucleation of HAp, the reason for which high phosphate and low calcium concentrations favor HAp formation more than the other way around 63 and are routinely used in biomimetic mineralization experiments 64 . As a result, the activation barriers for Ca 2+ and H x PO 4 x-3 ions differ and the crystal growth rate can be twice higher at high [H x PO 4 x-3 ]/[Ca 2+ ] ratios, even when the supersaturation ratio is the same 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Namely, Ca 2+ ions are more mobile than H x PO 4 x-3 ions, which tend to reside on surfaces longer and present the starting points for nucleation of CPs 59,60 . Per the Ostwald-Lussac rule, the growth of a most stable phase proceeds through successive growth and dissolution of less stable ones in the direction spanning from the least to the most stable.…”
Section: Discussionmentioning
confidence: 99%